Příprava stavební zakázky - Pilař, Matěj (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Předmětem bakalářské práce je analyzovat průběh přípravy a nabídku výstavby specializované stavební firmy. Úkolem práce je vyhodnocení získaných výsledků a zpracování návrhu možného zlepšení. Práce je rozdělena na teoretickou a praktickou část. V teoretické části se řeší problematika v obecné rovině a v té praktické se aplikuje na specializované stavební firmě.

In this thesis we analyse the preparation and proposition of construction for a specialised construction company. The goal of this thesis is evaluation of the obtained results and to suggest possible enhancements. The thesis is divided into two parts – theoretical and practical. In the theoretical part we analyse the issue generally, while we apply them to the specialised construction company in the practical part of this thesis.
Construction Order Preparation
Keywords: Projekt; projektové řízení; cíl projektu; životní cyklus projektu; stavební zakázka; strukturování projektu; organizace projektu; časové plánování projektu; projektová dokumentace; Project; management of project; project goal; the project life cycle; construction procurement; project structure; project organisation; project time planning; project documentation